Primary headache in the elderly in South-East Asia - Tai, M.L.; Jivanadham, J.S.; Tan, C.T.; Sharma, V.K. (2012)
Headache aetiology and presentation are considerably different in elderly individuals. However, literature on headache characteristics among Asians is limited. The objective of this study was to evaluate the headache characteristics among elderly in an outpatient clinic setting in Malaysia, a South-East Asian country with diverse ethnicity. In this prospective cross-sectional study, patients presenting with headache to Neurology and Primary Care Clinics of University Malaya Medical Centre between February 2010 and July 2010 were included. Data for consecutive eligible adult patients were entered in a prospective headache registry. International Headache Criteria II (ICHD-II) were used to classify various headache subtypes. Patients with headache due to intracranial space occupying lesions were excluded. Patient were divided into two age groups-elderly (55 years and above) and younger (less than 55 years of age). Of the 175 screened patients, 165 were included in the study-70 in elderly age group and 95 in younger group. Tension-type headache was the commonest subtype (45.7 %) among the elderly while Migraine without aura (54.7 %) was more common in young adults. More elderly patients suffered from chronic daily headache as compared to younger patients (47.1 vs. 28.4 %; p = 0.015). Headache subtypes and frequency differ considerably among elderly South East Asian patients.